2020
DOI: 10.1101/2020.02.13.945717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut bacterial deamination of residual levodopa medication for Parkinson’s disease

Abstract: 24Parkinson's disease is associated with gastrointestinal tract dysfunction, where constipation is reported 25 as the most common gastrointestinal symptom. Aromatic bacterial metabolites are attracting 26 considerable attention due to their implication on gut homeostasis and host's physiology. Clostridium 27 sporogenes is a key contributor to the production of these bioactive metabolites in the human gut. Here, 28we show that C. sporogenes effectively deaminate non-proteinogenic aromatic amino acids, such as 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, ex vivo rodent studies and in vivo dog and human studies showed an effect of dopamine agonists and/or dopamine (which can originate from levodopa in PD patients) on the gut motility, recently reviewed (van Kessel and El Aidy, 2019b, and citations in there). Gut microbial metabolization of unabsorbed residues of levodopa were also shown to influence ileal-motility ex vivo (van Kessel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ex vivo rodent studies and in vivo dog and human studies showed an effect of dopamine agonists and/or dopamine (which can originate from levodopa in PD patients) on the gut motility, recently reviewed (van Kessel and El Aidy, 2019b, and citations in there). Gut microbial metabolization of unabsorbed residues of levodopa were also shown to influence ileal-motility ex vivo (van Kessel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, we showed that the unabsorbed residues of levodopa that reach the distal small intestine is converted to a bioactive molecule, which reduces ileal contractility in mice ex vivo. 46 Nonetheless, whether PD medication per se is also associated with alterations in microbiota composition, small intestinal gut motility, and SIBO remains unknown.…”
Section: Introductionmentioning
confidence: 99%